Between abandonment and resilient thrusts in the mountain territories of the Orobie (Bergamo) - Alisia Tognon; Marco Bovati (Anuari d’Arquitectura i Societat)
This paper is part of a broader research project, which aims to explore multi-scale methods and strategies (from territorial to building scale) and multidisciplinary approaches to recover underused areas in the mountains of Northern Italy. For decades, these territories have suffered from high incidences of abandonment phenomena due to their proximity to metropolitan areas, leading to loss of care and an increase in territorial fragility. Nevertheless, they are rich in cultural meaning expressed it’s in the close relationship between natural and anthropogeographical landscapes. In this framework, identity value is an essential element for the protection and care of the territories themselves and as a planning tool to establish the resilience of these territories. This paper aims to focus on the area of the Highlands of Bergamo, which are complex places since they are almost close to the urban center of Milan, but are areas considered marginal in terms of wider logic. In fact, in the past years, the Orobic massif has been one of the main objects of industrial and tourist exploitation (the 1960s-80s), before suffering from abandonment phenomena that have forced and continue to push these areas to the point of major reconsideration. In this direction, the paper points out which are the most critical points to consider for the rebirth of these neglected mountains.